The TiO2/Ru(dcbpyH2)2(NCS)2/Au Schottky junction - Dittrich, Th. (2008)
Ru(dcbpyH2)2(NCS)2 molecules have specific binding sites for TiO2 and Au surfaces and a large dipole moment what makes them attractive for engineering of Schottky junctions. The rectification of the junction conditioned with a monolayer of Ru(dcbpyH2)2(NCS)2 molecules increased by several orders of magnitude in comparison to the bare TiO2/Au junction. The influence of (i) trap-assisted tunneling, of (ii) specific interaction of Ru(dcbpyH2)2(NCS)2 molecules with oxygen vacancies at the TiO2 surface and of (iii) the dipole moment of the Ru(dcbpyH2)2(NCS)2 molecules on the activation energy of the diode saturation current was demonstrated. The estimated projected dipole moment of one Ru(dcbpyH2)2(NCS)2 molecule amounted to about 5 D.